Influence of Laminate Orientation Ratio on the Tensile Strength of Sisal Fiber Composites - Ahmad Kholili Kuthut Widekso; Ahmad Dony Mutiara Bahtiar; Ahmad Dzulfikri Halimi (E-Journal Universitas Malikussaleh, 2026)
The development of natural fiber-based composite materials continues to increase due to their lightweight, environmentally friendly properties, and ability to provide good mechanical performance. Sisal fiber is one of the potential reinforcing candidates because it has high tensile strength and abundant availability; however, the performance of sisal fiber composites is greatly influenced by the lamination angle orientation, while research on lamination angle variations in epoxy composites is still limited. This study was conducted to examine the effect of sisal fiber lamination angle variations on the tensile strength of epoxy composites with orientations of 0°/90°/0°, 30°/-30°/30°, and 45°/-45°/45°. The composites were made using the hand lay-up method with a fiber volume fraction of 50%, while tensile testing was carried out in accordance with the ASTM D3039 standard. The results showed that the lamination angle had a significant effect on the mechanical properties of the composites. The 0°/90°/0° orientation provided the highest performance with a tensile strength of 98.403 MPa, strain of 9.457%, and elastic modulus of 1.061 GPa. The 30°/-30°/30° orientation produced a tensile strength of 9.957 MPa and a modulus of 0.577 GPa, while the 45°/-45°/45° orientation achieved 30.662 MPa and a modulus of 0.722 GPa. These findings confirm that fibers aligned parallel to the tensile direction contribute most significantly to the increase in the mechanical strength of composites. This research is expected to serve as a reference in selecting the optimal lamination configuration and support the development of strong, lightweight, and more sustainable natural fiber composite materials.